Mitral anular plane excursion predicts coronary stenosis during stress echocardiography with dipyridamole. (8th February 2021) - Moderato, L; Binno, S; Rusticali, G; Dallospedale, C; Aschieri, D; Pastorini, G; Piepoli, MF
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Dipyridamole stress echocardiography (DSE) is an important tool for detecting reversible ischemia in patients with suspected coronary artery disease (CAD); nonetheless, the results of the test are related to wall motion abnormalities, moderately operator-dependent, and left anterior descending (LAD) artery reserve, resulting in a moderate sensibility and specificity.  Purpose: Aim Of our study was to evaluate whether an easy-to-use parameter like mitral annular plane systolic excursion (MAPSE) could be useful to identify CAD during DSE.  Methods: We prospectively enrolled 512 patients that underwent DSE for suspected CAD; rest and peak MAPSE was acquired; 148 patients were referred to perform coronary angiography, with evidence of severe coronary stenosis in 91 patients.   The mean age was 66.7 ±11 years, male gender was prevalent (64%).  MAPSE at the peak was significantly different between patients with CAD and patient without (13, 4mm vs 16, 81 mm, p < 0.001); in fact, patients with CAD showed a blunted or no increase of MAPSE after dipyridamole infusion, with a significative difference in Delta Mapse (Mapse peak-Mapse rest) between groups ( -0.5mm vs 2.8mm) By using a Receiver Operating Curve, the Area under the curve was 0, 764 (0.682-0.846), with the best cut-off value of +0.5mm (Sensibility 77%, Specificity 62% - Figure 1), comparabale with traditional methods like LAD reserve, FE reduction or Wall Motion Score Index.  Discussion: to our knowledge, this is the first study that compared the behavior of MAPSE during dipyridamole infusion in patients with and without coronary artery disease. MAPSE is a well-known surrogate of longitudinal systolic function and has increased sensitivity over traditional methods of systolic performance such as LV-EF: in this context, dipyridamole induced reversible ischemia could affect prematurely MAPSE then EF or wall motion abnormalities. In our study, in patients with evidence of reversible ischemia during DSE, a blunted or no increase of MAPSE was able to predict CAD. Incorporating this easy-to-use parameter could improve the specificity of DSE and strengthen the suspect of reversible ischemia when clear wall motion abnormalities are not found.